(untitled) - George N Agrios (San Diego, California, 1997)
The book includes discoveries and improvements in molecular plant pathology, biological control, computers, and taxanomy of mocroorganisms, and the emergence of new plant pathogenetic microorganisms. Most improvements have been in the area of molecular genetics of plant disease resistance to pathogens
Thâm cứu chiến lược quản lý bệnh hại cây trồng,Tương tác giữa cây trồng và dịch hại,Anh văn chuyên môn - KHCT,Thâm cứu bảo vệ thực vật
Keywords: plant diseases